2014
DOI: 10.1155/2014/950190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfation on Zirconia-Pillared Montmorillonite to the Catalytic Activity in Microwave-Assisted Citronellal Conversion

Abstract: Preparation of sulfated zirconia-pillared montmorillonite was carried out in two steps; zirconia pillarization and sulfation to zirconia-pillared montmorillonite. The prepared materials were characterized by using X-ray diffraction (XRD), measurement of the specific surface area, total pore volume and pore size distribution by the N2adsorption method, scanning electron microscopy-energy dispersive X-ray (SEM-EDX), and surface acidity determination by using pyridine adsorption-FTIR analysis. The activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Because heterogeneous catalysts are less expensive, easier to prepare, regenerative, and reusable, citronellal cyclization was investigated in this work in a trickle-bed reactor over extrudates comprising β or Y zeolites. Cyclization of citronellal has been previously intensively studied in batch reactors over different acidic catalysts, such as zeolites, , mesoporous materials, , metal-modified zeolites, mixed oxides, , heteropoly acids, montmorillonite-supported heteropoly acids, MCM-41-supported heteropoly acids, heterogeneous metal–organic frameworks, carbon nanotubes, sulfated zirconia-pillared montmorillonite, and zirconium β zeolite . The temperature range is between 0 and 100 °C, ,,,, and hydrophobic solvents, such as cyclohexane, toluene, ,, dichloromethane, , and benzene, are often used.…”
Section: Introductionmentioning
confidence: 99%
“…Because heterogeneous catalysts are less expensive, easier to prepare, regenerative, and reusable, citronellal cyclization was investigated in this work in a trickle-bed reactor over extrudates comprising β or Y zeolites. Cyclization of citronellal has been previously intensively studied in batch reactors over different acidic catalysts, such as zeolites, , mesoporous materials, , metal-modified zeolites, mixed oxides, , heteropoly acids, montmorillonite-supported heteropoly acids, MCM-41-supported heteropoly acids, heterogeneous metal–organic frameworks, carbon nanotubes, sulfated zirconia-pillared montmorillonite, and zirconium β zeolite . The temperature range is between 0 and 100 °C, ,,,, and hydrophobic solvents, such as cyclohexane, toluene, ,, dichloromethane, , and benzene, are often used.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced amount of silica and alumina could probably due to some leaching during filtration and cal- Figure 1. X-ray diffractograms for unmodified and Cu 2+ modified MMT K10 cination processes [20]. Based on the previous works, it was revealed from the diffuse reflectance UV-vis spectrum that Cu exists as Cu 2+ in MMT clay structure as Cu-MMT K10 exhibited a strong band with a maximum at 549 nm which is attributed to the d-d transitions of Cu(II).…”
Section: Energy-dispersive X-ray Spectroscopy Analysis (Edx)mentioning
confidence: 94%
“…The increasing quantity and distribution of surface acidity can be achieved by dispersion in a clay support via pillarization. Zirconium-pillared montmorillonite (Zr/MMT) demonstrated the increased surface acidity that was in line with the increased citronellal conversion into isopulegol, according to Fatimah et al, 2014. Moreover, the surface acidity enhancement was achieved by sulfation into the form of sulfated-Zr/MMT (S-Zr/MMT).…”
Section: Clay-based Heterogeneous Catalystsmentioning
confidence: 96%
“…The results of research by Chuah et al, 2001 showed that zirconium hydroxide and zirconium phosphate catalysts also have activity and selectivity in the cyclization reaction of citronellal to isopulegol. The presence of Lewis and Bronsted acid catalyst sites is very important in the citronellal cyclization reaction, as depicted in the reaction mechanism proposed in Figure 5 (Álvarez-Rodríguez et al, 2012;Fatimah et al, 2014;Ravasio et al, 2000;Sudiyarmanto et al, 2017).…”
Section: Citronellal Conversion Into Isopule-golmentioning
confidence: 99%